БИОКЛИМАТИЧЕСКИЕ ОСОБЕННОСТИ ПЕРМСКОГО КРАЯ КАК ОСНОВА ДЛЯ РАЗВИТИЯ МЕСТНОГО КЛИМАТОЛЕЧЕНИЯ (Географический вестник=Geographical bulletin, 2017)
Рассматриваются особенности использования биоклиматического потенциала в целях лечебно-оздоровительной рекреации. Приводятся результаты анализа основных возможностей организации местного климатолечения. Приведена курортологическая классификация биоклимата и погод.К л ю ч е в ы е с л о в а: биоклимат; климат; климатолечение; рекреацияBIOCLIMATIC POTENTIAL OF PERM REGION AS A BASE OF DEVELOPMENT OF THERAPEUTIC AND CLIMATIC TREATMENT In the article a brief bioclimatic characteristic and an assessment of bioclimatic potential ofPermregion are adduced Ust-Kachka health resort zone is given as an example. The main health resort treatment regimes are considered. The optimal conditions and possibilities of using of climatic factor of flat territory in therapeutic purposes are offered.K e y w o r d s: climate; bioclimate; climatic treatment; recreation; resort-recreational zone; resort.